2001
DOI: 10.1099/00221287-147-2-345
|View full text |Cite
|
Sign up to set email alerts
|

The aprX–lipA operon of Pseudomonas fluorescens B52: a molecular analysis of metalloprotease and lipase production The GenBank accession numbers for the sequences reported in this paper are AF216700, AF216701 and AF216702.

Abstract: Extracellular protease and lipase production by psychrotrophic strains of Pseudomonas fluorescens is repressed by iron and regulated by temperature. The regulation of protease and lipase has been investigated in P. fluorescens B52. Whereas lipase production is increased below the optimum growth temperature (' low-temperature regulation '), protease production was relatively constant and only decreased above the optimum growth temperature. The genes encoding protease (aprX) and lipase (lipA) are encoded at oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 37 publications
3
60
0
Order By: Relevance
“…The model protein for the RTX family, alpha-hemolysin, inserts into host membranes and forms pores that allow an influx of Ca 2ϩ into host cells, altering host physiology or leading to cell death (37). Additional RTX family members have displayed a wide array of functions in bacterial pathogens; secreted proteases (24,29) and lipases (9,40), cross-linkers of cellular actin that cause host cell rounding (28), and surface-associated coats of protein that form the bacterial S-layer (26,30) represent a few examples of these diverse functions. However, most RTX family members remain uncharacterized.…”
mentioning
confidence: 99%
“…The model protein for the RTX family, alpha-hemolysin, inserts into host membranes and forms pores that allow an influx of Ca 2ϩ into host cells, altering host physiology or leading to cell death (37). Additional RTX family members have displayed a wide array of functions in bacterial pathogens; secreted proteases (24,29) and lipases (9,40), cross-linkers of cellular actin that cause host cell rounding (28), and surface-associated coats of protein that form the bacterial S-layer (26,30) represent a few examples of these diverse functions. However, most RTX family members remain uncharacterized.…”
mentioning
confidence: 99%
“…Protease production by Y. ruckeri (46), Flavobacterium psychrophilum (47) and lipase production by Pseudomonas fluorescens (11,54) has been also demonstrated to be higher at temperatures below the optimal growth temperature. Despite the mechanisms of regulation by temperature are poorly understood, Woods et al (54) suggested that on lipase production by P. fluorescens a posttranscriptional or posttranslational regulation mechanism is involved. In this bacterium, the gene for lipase (lipA) is part of the aprX-lipA operon that includes the genes for a metalloprotease (aprX), for a protease inhibitor and for type I secretion functions.…”
Section: Discussionmentioning
confidence: 99%
“…AJ007827). In P. fluorescens B52, Woods et al (2001) reported that expression of the serralysin-type metalloprotease gene, aprX, was negatively regulated by iron at the transcriptional level. While the authors suggested the possible involvement of a PbrA homologue, they were unable to test this hypothesis, as they failed to isolate a pbrA insertion mutant of this strain.…”
Section: Introductionmentioning
confidence: 99%